Thrombotic Microangiopathy as an Emerging Complication of Viral Vector–Based Gene Therapy - Nora Schwotzer; Carine El Sissy; Isabelle Desguerre; Véronique Frémeaux-Bacchi; Laurent Servais; Fadi Fakhouri (Kidney International Reports, 2024)
Gene therapy has brought tremendous hope for patients with severe life-threatening monogenic diseases. Although studies have shown the efficacy of gene therapy, serious adverse events have also emerged, including thrombotic microangiopathy (TMA) following viral vector–based gene therapy. In this review, we briefly summarize the concept of gene therapy, and the immune response triggered by viral vectors. We also discuss the incidence, presentation, and potential underlying mechanisms, including complement activation, of gene therapy-associated TMA. Further studies are needed to better define the pathogenesis of this severe complication of gene therapy, and the optimal measures to prevent it.